Is EMG of the Lower Leg Dependent on Weekly Running Mileage? - Baur, H.; Hirschmüller, A.; Müller, S.; Cassel, M.; Mayer, F. (International Journal of Sports Medicine, 2012)
Neuromuscular activity of the lower leg is dependent on the task performed, speed of movement and gender. Whether training volume influences neuromuscular activity is not known. The EMG of physically active persons differing in running mileage was analysed to investigate this. 55 volunteers were allocated to a low (LM: < 30 km), intermediate (IM: > 30 km & < 45 km) or high mileage (HM: > 45 km) group according to their weekly running volume. Neuromuscular activity of the lower leg was measured during running (3.33 m·s − 1). Mean amplitude values for preactivation, weight acceptance and push-off were calculated and normalised to the mean activity of the entire gait cycle.Higher activity in the gastrocnemius group was observed in weight acceptance in LM compared to IM (+30%) and HM (+25%) but lower activity was present in the push-off for LM compared to IM and HM. For the peroneal muscle, differences were present in the push-off where HM showed increased activity compared to IM (+24%) and LM (+60%). The tibial muscle revealed slightly lower activity during preactivation for the high mileage runners. Neuromuscular activity differs during stance between the high and intermediate group compared to low mileage runners. Slight adaptations in neuromuscular activation indicate a more target-oriented activation strategy possibly due to repetitive training in runners with higher weekly mileage.
Keywords: locomotion; neuromuscular control; running gait; training volume